Digitalization and robotization in the preparation of cytostatics at the hospital pharmacy in Oslo - Savić, Vedrana (Archives of Pharmacy, 2022)
There is a significant increase in the need for preparation of injections and infusions with cytostatics that are individualized according to the patients' needs. The compounding of such drugs carries a risk to patient safety (correct dose, compatibility, microbiological contamination) and employee safety (unnecessary exposure to cytostatics). Therefore, hospital pharmacies are increasingly taking over the preparation of individualized cytostatic therapy. In order to achieve the highest efficiency and quality in the cytostatic drugs compounding, special softwares are used, enabling the physician to order the treatment, and the pharmacist then controls the dosage, compatibility and preparation of the drug. During the compounding of these drugs, all necessary procedures are on the screens, and the operator can confirm that each key operation was performed correctly. Scanning codes on raw materials reduces the possibility of usage of wrong ingredients, while scanning the code on the prepared medicine and the patients' personal code reduces the risk of administering the medicine to the wrong patient. In addition to the softwares, a production robot is used which enables a significant increase in production capacity. However, the possibilities of robots are currently limited and cannot completely replace humans, especially when it comes to compounding of innovative drug carriers. Digitization and robotization can significantly improve the efficiency in the preparation of cytostatics and ensure product quality and patient safety. However, it is very important to keep in mind that it is necessary to conduct regular tests and revalidate the processes to ensure the proper functioning of these systems.